The office development process in Kuala Lumpur : an application of the structure and agency approach - 457751 Maziah Ismail (Aberdeen : University of Aberdeen, 1994)
In this study, a theoretical framework within the structure and agency philosophical perspective is presented to aid understanding of the land development process. In order to demnostrate how such a theoretical framework may be used, the study focusses on three case studies consisting of high rise office developments in the Golden Triangle Area of Kuala Lumpur. It is argued that traditional models of the land development process are unable to explain adequately the structure and processes of the builit environment. Hence, the principal reason for undertaking the study was to assess teh suitability of the structure and agency approach to explain tha land and property development process in a fuller context. In this study, there are two problems. First, to formulate a set of hypotheses in relation to the factors driving the office development process in Kuala Lumpur. The hypotheses concern the interests and strategies of individual agents involved in the development process and the way the underlying structural factors affect and change with changing agents actions and interactions. Second, to asses whether Healey's (1992) model of the land development process, which is used as a means to approach this research, is a relevant device to carry out empirical studies on the land development process. It is concluded that, in general, teh office development process involves complex institutional and agency relationships.The office develpment process in Kuala Lumpur is shaped by the form of economic and institutional structure which influenced the interests and the way agents behaved in deplying resources. One important finding is that this research is difficult to undertake. The diffulculty lies not only in the complexity of the office developments under study, but also resulted from the deficiency of Healey's (1992) model. Thus , it can be concluded that although Healey has provided an important dialogue between concern on structure and those on agency, and provided a 'blueprint' for how should studies on land development process be carried out, empirically, the model proposed is excessively abstract and ought to be further developed in such a way so as to achieve a more immediate relevance for empirical work.